2012
DOI: 10.1080/10686967.2012.11918080
|View full text |Cite
|
Sign up to set email alerts
|

The Role of National Culture on Relationships Between Customers' Perception of Quality, Values, Satisfaction, and Behavioral Intentions

Abstract: The purpose of this paper is to examine the influence of individualistic cultures (such as the American culture) and collectivistic cultures (such as the Chinese culture) on the interrelationship among service quality, food quality, perceived value, customer satisfaction, and behavioral intentions in the fast-food industry. First, the authors provide empirical evidence of the robust relationships among the constructs across diverse cultures. Second, they investigate how moderator variables such as customer age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 46 publications
0
12
0
8
Order By: Relevance
“…Di sisi lain kualitas makanan berpengaruh secara signifikan terhadap kepuasan pelanggan, demikian juga halnya dengan harga/nilai (price/value). Sehingga dapat dikatakan bahwa kualitas makanan dan harga/nilai memiliki pengaruh signifikan terhadap niatan perilaku konsumen dengan dimediasi oleh peubah kepuasan pelanggan Wen et al (2012) menguji pengaruh budaya individualistik orang Amerika dan budaya kolektivistik orang China terhadap interrelasi kualitas layanan, kualitas makanan, nilai yang dirasakan, kepuasan pelanggan, dan niatan perilaku konsumen di industri makanan siap saji. Mereka menguji bagaimana budaya nasional sebagai moderator sangat berpengaruh pada hubungan peubah-peubah tersebut.…”
Section: Pendahuluanunclassified
See 2 more Smart Citations
“…Di sisi lain kualitas makanan berpengaruh secara signifikan terhadap kepuasan pelanggan, demikian juga halnya dengan harga/nilai (price/value). Sehingga dapat dikatakan bahwa kualitas makanan dan harga/nilai memiliki pengaruh signifikan terhadap niatan perilaku konsumen dengan dimediasi oleh peubah kepuasan pelanggan Wen et al (2012) menguji pengaruh budaya individualistik orang Amerika dan budaya kolektivistik orang China terhadap interrelasi kualitas layanan, kualitas makanan, nilai yang dirasakan, kepuasan pelanggan, dan niatan perilaku konsumen di industri makanan siap saji. Mereka menguji bagaimana budaya nasional sebagai moderator sangat berpengaruh pada hubungan peubah-peubah tersebut.…”
Section: Pendahuluanunclassified
“…Model konseptual ini merupakan integrasi model konseptual Ha dan Jang (2012), Qin dan Prybutok (2008) dan Wen et al (2012). Ha dan Jang (2012) menguji model konseptual pengaruh atmosferik terhadap niatan perilaku konsumen yang dimediasi oleh kualitas layanan dan kualitas makanan.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…More completely, table 1 shows some service quality models that are specifically designed for measuring service quality in fast food restaurant. [14] Assurance and empathy, food cleanliness, responsiveness, reliability, and tangibles Qin et al [12] Recoverability, assurance, tangibles, empathy, responsiveness, and reliability Wen et al [11] Recoverability, assurance, tangibles, empathy, responsiveness, and reliability Campos and Nobreda [31] Dimensions were identified to be different in each stage customer must perform to obtain fast food. Yunus et al [36] assurance, tangibles, empathy, responsiveness, reliability, low food prices, short service time and convenient location Based on the previous explanation, it can be concluded that researchers who discussed fast food restaurant service by involving service quality dimensions that represents the performance of service companies in satisfying Muslim customer needs related to Islamic values is very limited.…”
Section: Fast Food Service Quality Modelmentioning
confidence: 99%
“…Referring to the explanation on the previous paragraph, a fast food restaurant needs to monitor and improve its service quality in order to win business competition [9,10]. Furthermore, empirical researches have proved that fast food restaurant service quality positively affects customer satisfaction [11,12,13,14], revisit intention [13,15] and customer's purchasing decision [16].…”
Section: Introductionmentioning
confidence: 99%